Rituximab‐refractory thrombotic thrombocytopenic purpura responsive to intravenous but not subcutaneous bortezomib. Issue 4 (18th January 2016) - Patel, Priyank P.; Becker, Joanne; Freyer, Craig; Griffiths, Elizabeth; Thompson, James E.; Wang, Eunice S.
Abstract : BACKGROUND: Thrombotic thrombocytopenic purpura (TTP) is often characterized by formation of antibodies against a disintegrin and metalloprotease with thrombospondin repeat, member 13 (ADAMTS13). Therapeutic plasma exchange (PEX) is the basis of TTP therapy, with additional immunosuppression to eradicate ADAMTS13 antibody–producing B cells. CASE REPORT: We describe a case of a 22‐year‐old female with TTP refractory to PEX, high‐dose corticosteroid therapy, and rituximab. Laboratory blood tests showed a severe ADAMTS13 deficiency and the presence of an inhibitor. Although one cycle of subcutaneous bortezomib resulted in clinical improvement, the patient remained PEX dependent. A second course of intravenous (IV) bortezomib resulted in a complete remission without evidence of relapse after 18 months. CONCLUSION: This case confirms the efficacy of bortezomib for refractory TTP and suggests that the in vivo activity of IV bortezomib may be distinct from subcutaneous drug in this setting.